Spontaneous Endometrial Cast Expulsion in Membranous Dysmenorrhoea: A Case Report - Swapnali Sansare; Aneesha Nallapati (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Membranous dysmenorrhoea is a rare gynaecological condition characterised by the expulsion of the endometrium as a single intact cast that retains the shape of the uterine cavity. The authors report the case of a 36-year-old multiparous female who presented with a history of heavy and prolonged menstrual bleeding associated with the passage of tissue per vaginum for 7-8 months. She had a preceding history of amenorrhoea for six months and pregnancy was excluded. Clinical examination revealed expulsion of a membranous structure through the cervix; it was removed, resulting in immediate symptomatic relief. Ultrasonography (USG) demonstrated a thickened endometrium with no focal uterine or adnexal pathology. Histopathological examination confirmed the diagnosis, showing pre-decidualised endometrial tissue with dilated, congested vessels. The patient remained asymptomatic on follow-up over three menstrual cycles. Membranous dysmenorrhoea remains a poorly understood entity with limited reported cases, often associated with hormonal influences, though spontaneous occurrences, as seen in the present case, are uncommon. Recognition of this condition is important to differentiate it from other causes of abnormal uterine bleeding and to avoid unnecessary interventions.